(untitled) (Research, Society and Development, 2020)
This article refers to an investigation developed from a project applied to a class of students in the 5th year of elementary school, with the aim of understanding the importance of the rules of coexistence and respect, with a view to the development and improvement of understanding of skills through playful strategies. This project sought to emphasize improvements in the teaching-learning process through the game of marbles, as well as enabling socialization mechanisms for those who had relationship difficulties, both inside and outside the classroom. To this end, a regiment was drafted together, containing the rules for each phase of the work, and, in detail, the nuances pertinent to the execution of activities, since there were some students in that class who had relationship difficulties, which end up interfering in the concentration, production, understanding and resolution of activities. The work is of a qualitative nature, using the technique of observation and bibliographic research. At the end of the aforementioned project and on-site observations, it was concluded that satisfactory results were achieved, as it was found that play is a serious thing, and as simple as it is if directed, planned and organized, it can be a great device for development students’ teaching-learning and socialization process.